Core, shapley value, nucleolus and nash bargaining solution: A Survey of recent developments and applications in operations management. (July 2022) - Luo, Chunlin; Zhou, Xiaoyang; Lev, Benjamin
Highlights: We review the recent theoretical developments and applications in operations management of the core, Shapley value, nucleolus and Nash bargaining solution. We classify the literature of applications in operations management into deterministic and stochastic models, horizontal cooperation and vertical cooperation modes. The future research directions of the theoretical developments and applications in operations management of the four solution concepts are proposed. Abstract: The core, Shapley value, nucleolus and Nash bargaining solution are the most widely used solution concepts in cooperative game theory. This paper surveys the literature on recent developments of these solution concepts and applications in operations management. Firstly, we briefly introduce the basic concepts and recent theoretical developments of the four solution concepts. Secondly, we review the applications in operations management in the past decade. Based on the problem properties, we classify the literature into deterministic and stochastic models, horizontal cooperation and vertical cooperation modes. Lastly, we discuss the future research directions with applications in operations management, which are hoped to contribute to the literature by enhancing the applications of cooperative game theory in operations management.